Electromyographic evaluation of muscle firing patterns in the ridden horse during jumping as an objective method of informing current jump training programmes - St George, L. B. (University of Central Lancashire, 2017)
The sport of show jumping (SJ) places great physical demands on the equine athlete. Despite this, selection and training strategies for the equine jumping athlete are largely based on anecdotal methods. SJ horses are generally selected at a young age based on quality of movement and jump technique. Numerous studies have provided information on the biomechanical demands of jumping. However, research has not sufficiently investigated how quality jump technique and performance may be improved through training in the SJ horse. The horse`s ability to execute the physical demands required for SJ is greatly influenced by muscular adaptation to training. Scientifically evidenced training programmes incorporate exercises, which mimic the duration, intensity, neuromuscular activity and movement patterns that are experienced during competition. However, a lack of understanding on how equine muscles facilitate the jumping effort represents a major gap in knowledge. Therefore, the aim of this thesis was to explore muscle firing patterns, which facilitate "quality" movement during different phases of the equine jump and to determine whether these support traditional training methods in the jumping horse. Surface electromyography (sEMG) and three-dimensional (3D) kinematic data were collected synchronously from a group of elite and non-elite jumping horses during canter and jump trials over a 1.0m fence. sEMG data were collected from the Superficial Gluteal, Biceps Femoris (vertebral head), Triceps Brachii (long head), Trapezius (cervical head), and Splenius. Lack of standardised methods within equine sEMG research represents a major gap in knowledge. Therefore, four original studies were conducted to develop optimal methods for the acquisition and analysis of sEMG data collected from equine subjects during jumping. These methods were employed in the main study of the thesis. An original questionnaire was designed to define "quality" movement and "traditional" training methods in the jumping horse, based on the opinions and preferences of highly qualified equestrians. Questionnaire results revealed obvious preferences for specific movement traits, which were used to inform kinematic data analysis. The incorporation of questionnaire findings ensured that research had practical application within the equine industry. Kinematic data analysis in the main study of the thesis revealed that "quality" movement traits between elite and non-elite athletes were largely non-significant. These findings suggested that movement alone may not be an accurate method for differentiating between good and poor jump technique and performance. However, sEMG data revealed differences in neuromuscular strategies between groups, which had a direct influence on jump technique. Elite horses exhibited the greatest capacity for generation of muscular force and power, particularly in the hindlimb during jump take-off. This finding was evidenced by greater: integrated EMG (iEMG), average rectified value, and peak amplitude data. As a result, "quality" jump technique was facilitated through greater vertical displacement and velocity of the centre of mass (CM) during jump take-off and suspension phases. These findings provide objective evidence for equestrians to place greater emphasis on strength (anaerobic training), as questionnaire findings revealed a trend for largely aerobic training programmes in the jumping horse. Findings also suggest that equestrians prioritise movement traits, which are indicative of muscular strength when selecting equine jumping athletes. This study has demonstrated the benefits of sEMG for the development of scientifically evidenced training and selection processes in the equine SJ athlete.